1998
DOI: 10.1046/j.1365-3016.12.s2.1.x
|View full text |Cite
|
Sign up to set email alerts
|

The practice of antenatal care: comparing four study sites in different parts of the world participating in the WHO Antenatal Care Randomised Controlled Trial

Abstract: Summary. In the preparation of a randomised controlled trial to evaluate a new programme of antenatal care (ANC) in different parts of the world, we conducted a baseline survey of the ANC procedures in all 53 clinics participating in the trial. There were two components of this survey: (1) description of clinic characteristics and services offered: the staff of each clinic was interviewed and direct observation was made by field supervisors, and (2) the actual use of services by pregnant women attending these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In Ghana 85% attended at least one antenatal visit with a skilled provider before delivery. Seventy-three percent of pregnant women in urban areas and 55% in rural areas were more likely to attend 4 or more antenatal visits [6, 16]. Though it has been reported that up to 40% of pregnant women in developing countries receive no ANC [17], a study in Ghana reported that 14% of women did not attend ANC at all [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana 85% attended at least one antenatal visit with a skilled provider before delivery. Seventy-three percent of pregnant women in urban areas and 55% in rural areas were more likely to attend 4 or more antenatal visits [6, 16]. Though it has been reported that up to 40% of pregnant women in developing countries receive no ANC [17], a study in Ghana reported that 14% of women did not attend ANC at all [6].…”
Section: Introductionmentioning
confidence: 99%
“…The design and methodology of this survey is described elsewhere in this Supplement. 28 Tables 4 and 5 present the characteristics of the 53 clinics randomised to the intervention and control groups, using data from the antenatal care content survey at the clinic level. Clinics are mostly urban (n = 41), all belonging to the public health system and part of a polyclinic (n = 39) or within a hospital (n = 14).…”
Section: Baseline Surveymentioning
confidence: 99%
“…3 The alternatives being compared are a new model of antenatal care, developed by experts, and the baseline model of antenatal care as currently implemented in the selected sites. The baseline models differ to some degree between the study sites, 22 which may affect estimated differences between costs of the two programmes of care in the four trial centres. For example, the average number of visits in the baseline model of antenatal care varies from roughly four routine visits per women in Argentina to over eight in Cuba.…”
Section: What Are the Treatment Alternatives?mentioning
confidence: 99%
“…Socio-economic and epidemiological indicators collected alongside the trial show that women participating in the trial are likely to represent the majority of women eligible for routine pregnancy care in the participating countries. 22 The advantage of the cluster design for the economic evaluation is that the unit of randomisation is also a key unit of health management and cost generation.…”
Section: What Are the Treatment Alternatives?mentioning
confidence: 99%
See 1 more Smart Citation